Hysteroscopic resection of type 3 myoma: a new challenge?. (October 2016) - Capmas, Perrine; Voulgaropoulos, Audrey; Legendre, Guillaume; Pourcelot, Anne-Gaelle; Fernandez, Hervé
Abstract: Objective: Type 3 myomas are intramural within contact with the endometrium but lack any cavity deformation. There is no guideline for management of symptomatic type 3 myoma. The aim of this study was to evaluate the feasibility of symptomatic type 3 myoma hysteroscopic resection. Method: This retrospective study included symptomatic women (mainly pain, infertility or bleeding) who obtained an operative hysteroscopy for type 3 symptomatic myoma from June 2010 to December 2014 in the gynaecological unit of a teaching hospital. Result: Thirteen women with an operative resection using bipolar electrosurgery of type 3 myoma during the study period (June 2010 to December 2014) were included in the study. Two women had a hysterectomy 6 and 12 months after the procedure and one woman had an open myomectomy 30 months after the procedure for the recurrence of abnormal bleeding. Postoperative office hysteroscopy show a postoperative synechiae in 3 women out of 8. Incomplete resection was also obtained in 3 women out of 8. Conclusion: Hysteroscopic resection is a potential alternative to traditional surgery for type 3 myoma. This procedure must be confined to skilled surgeons because it is a difficult procedure. A postoperative office hysteroscopy is recommended in women of reproductive age.